2001
DOI: 10.1097/00001756-200102120-00012
|View full text |Cite
|
Sign up to set email alerts
|

Phonological aspects of word recognition as revealed by high-resolution spatio-temporal brain mapping

Abstract: We describe, for the first time, the use of high-resolution event-related brain potentials (hrERP) to identify the spatio-temporal characteristics of neural systems involved in phonological analysis. Subjects studied a visual word/non-word that was followed by the brief presentation of a prime letter (e.g. House, M) with the instruction to anticipate the word/non-word formed by replacing the word's first letter with the prime letter. After the prime letter, an auditory target word/non-word was presented that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
37
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 21 publications
17
37
1
Order By: Relevance
“…When the sentence-ending words were both phonologically and semantically unexpected, both PMN and N400 responses were elicited, and, in the opposite case, neither the PMN nor N400 responses were obtained. In agreement with this study, a PMN response, independent of the N400, has been obtained whenever a violation against the expected auditory phonemic features has been introduced [5,6,8,22,24,31].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…When the sentence-ending words were both phonologically and semantically unexpected, both PMN and N400 responses were elicited, and, in the opposite case, neither the PMN nor N400 responses were obtained. In agreement with this study, a PMN response, independent of the N400, has been obtained whenever a violation against the expected auditory phonemic features has been introduced [5,6,8,22,24,31].…”
Section: Introductionsupporting
confidence: 87%
“…However, this process appears to be insensitive to semantic top-down effects since words not embedded in a sentence [5,6] and non-words [6] also elicit the PMN. A non-semantic paradigm in which participants were instructed to expect a word/non-word that rhymed with a presented word/non-word and began with a certain sound produced enhanced PMNs to mismatches in both word and non-word conditions [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because the amplitude of this early negative shift varied as a function of the congruence of the word initial phoneme(s) with the contextually most expected word, Connolly and Phillips (1994) labeled this the phonological mismatch negativity or PMN. In a more recent study, they combined high density EEG and MEG to model the possible sources of the PMN and they concluded that it may have a left anterior source (Connolly et al, 2001). This finding was further bolstered with the results of an fMRI study (D'Arcy et al, 2004).…”
Section: Erp Studies Of Spoken Word Recognitionmentioning
confidence: 99%
“…However, in their 1994 study, the ERPs were obtained from 5 electrodes, and the authors were therefore not able to identify if the topographic distribution of the early negative shift was different from that of the N400, something that was clearly established in the present study. More recent studies of Connolly and colleagues (Connolly et al, 2001;D'Arcy et al, 2004) with high density ERP/MEG and fMRI have modeled a possible left anterior source of the PMN. However, in these studies, word priming paradigms were used instead of sentence contexts, and as has been shown in the present study, these two types of contexts may have differential effects on processing.…”
Section: Spoken Word Recognition In Sentencesmentioning
confidence: 99%